KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN DAERAH KABUPATEN BATU BARA TAHUN 2018-2021 - Rumapea, Masnida Elawati; Sembiring, Yan Christin; Saragih, Afni Eliana (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to find out how big the contribution of local taxes is to the local revenue of Batu Bara Regency. The population of this study is the realization of local taxes and the realization of local revenue at the Regional Revenue Agency of the Batu Bara Regency. The sample for this research is Regional Tax data and Regional Original Revenue data for 2018-2021 at the Regional Revenue Agency of Batu Bara Regency. The analytical method used is descriptive analysis with the contribution rate formula. Based on the results of the research, it shows that the average contribution realization for 2018-2021 is Hotel Tax, Entertainment Tax, Street Lighting Tax, Parking Tax, Swallow's Nest Tax, Non-Metal Mineral Tax and Acquisition Tax is better than the average realized contribution in 2014-2017 while the Restaurant Tax, Advertising Tax, Land Water Tax and Land and Building Tax are not better. For the average budget and realized contributions for 2018-2021 Entertainment Tax, Advertising Tax, Street Lighting Tax, Parking Tax, Groundwater Tax and Non-Metal and Rock Mineral Tax and Acquisition Tax fulfill the budget while Hotel Tax, Restaurant Tax, Sarang Tax Swallow, Land and Building Tax do not meet the budget and of the eleven Regional Taxes that are classified as